Elevated Serum Level of Interleukin 17 in a Population With Prehypertension. Issue 10 (3rd July 2015) - Yao, Wei; Sun, Yuemin; Wang, Xuechun; Niu, Kaijun
<x xml:space="preserve">Abstract</x> Cytokines play an important role in the pathogenesis of hypertension. The authors hypothesized that interleukin 17 (IL‐17) might contribute to the prehypertensive state. This study evaluated the relationship between serum levels of IL‐17 and prehypertension. A total of 394 participants were enrolled, after excluding for hypertension or treated hypertension, and divided into two groups (optimal blood pressure [BP] and prehypertension) based on the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure classification of BP. Optimal BP was defined as systolic BP <120 mm Hg and diastolic BP <80 mm Hg. Prehypertension was defined as systolic BP of 120 to 139 mm Hg or diastolic BP of 80 to 89 mm Hg. IL‐17A levels were determined by enzyme‐linked immunosorbent assay. The mean serum IL‐17 concentration in the prehypertension group was significantly higher than in the optimal BP group. The cohort was divided into quartiles Q1 (≤3.5 ng/L), Q2 (3.60 to 6.10 ng/L), Q3 (6.20 to 10.00 ng/L), and Q4 (≥10.10 ng/L) based on IL‐17 levels. The Q2 to Q4 groups had increasing odds ratios for having prehypertension compared with the Q1 group. Elevated serum IL‐17 was accompanied by a rise in systolic BP. Thus, increased serum IL‐17 levels are associated with prehypertension.